THE Effect of Profitability, Liquidity, and Free Cash Flow on the Value of LQ45-Indexed Companies on the Indonesia Stock Exchange - Isroah Isroah; Hana Dewi Artiqah Khoir (Universitas Negeri Yogyakarta, 2026)
Abstract This study examines the effects of Return on Assets (ROA), Current Ratio (CR), and Free Cash Flow (FCF) on firm value, measured by Price to Book Value (PBV), in LQ45 companies. Using a quantitative causal-comparative design, 154 firm-year observations were selected through purposive sampling and analyzed using multiple linear regression. The results show that ROA has a positive but insignificant effect on PBV, while CR has a negative and insignificant effect. FCF has a positive and significant effect on PBV. These findings indicate that free cash flow is the main financial factor associated with firm value in the observed sample. Effective free cash flow management may therefore strengthen investor confidence and market valuation.